Autologous stem cell transplantation in multiple myeloma in the era of novel drug induction: a retrospective Single-Center Analysis - Thoennissen, Gabriela B.; Görlich, Dennis; Bacher, Ulrike; Aufenberg, Thomas; Hüsken, Anne-Christin; Hansmeier, Anna Antonia; Evers, Georg; Mikesch, Jan-Henrik; Fritz-Kebede, Fleur; Bokemeyer, Carsten; Müller-Tidow, Carsten; Stelljes, Matthias; et al. (Acta haematologica, 2017)
Autologous stem cell transplantation; Induction therapy ; Melphalan high-dose chemotherapy; Multiple myeloma ; Novel compounds; Tandem autologous stem cell transplantation